PERSEPSI MASYARAKAT TERHADAP GANGGUAN GAJAH SUMATERA ( Elephas maximus sumatranus ) DI KABUPATEN OGAN KOMERING ILIR - Anita Rianti; Raden Garsetiasih (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
Research of elephant conflict with community have been conducted in Sungai Menang District, Ogan Komering Ilir Regency, South Sumatera Province. This study was conducted in three villages in September through December 2015. This study aimed to identify the perception and socio-economic characteristics of the community related to the conflict towards elephant conservation value. Data was collected through structured interview, while respondents were selected intentionally (purposive sampling). The results are shown that the level of community education in the village of Gajah Mati dan Gajah Mulya are low, 51% and 47% respectively, which are elementary school graduates, while the level of education in the village of Gajah Mukti is 58% of high school graduates. The majority of respondents are in productive age classes and worked as a farmer. The average income per month of people in the village of Gajah Mati is Rp1,814,583, while in Gajah Mukti and Gajah Mulya Village are Rp1,158,750 and Rp1,060,833 respectively. Elephants disturbance occur in all respondent villages and has an impact on the community perception of the elephant conservation becomes negative. Most respondents want that the elephants are relocated to Padang Sugihan Wildlife Sanctuary which is suitable for the habitat of the elephants.